Correlation Between Caries Status and Quality of Life Among Elderly at Dangung-Dangung Public Health Center - Kournikova, Lianka Pamelia; Elianora, Dewi; Surya, Leny Sang (Jurnal Pustaka Medika (Pusat Akses Kajian Medis dan Kesehatan Masyarakat), 2025)
Global demographic changes are increasing the number of elderly people at risk of experiencing significant oral health problems. Dental caries (DMF-T) is a major issue in the elderly caused by decreased oral hygiene, which can potentially lower their quality of life. Objective This study aims to analyze the relationship between dental caries status and quality of life in the elderly at Dangung-Dangung Health Center, Payakumbuh. Method This quantitative study with a cross-sectional approach was conducted in 2018 at Dangung-Dangung Health Center, Payakumbuh. The study sample consisted of 35 elderly people selected based on inclusion and exclusion criteria. Caries status was measured using the DMF-T index, while quality of life was measured using the OHIP-14 questionnaire. Data analysis was performed using Pearson correlation test (p < 0.05). Result The study results showed an average DMF-T index of 23.20 ± 4.70 and an average OHIP-14 score of 26.57 ± 8.98. There is a significant positive relationship with a strong correlation strength between the DMF-T index and OHIP-14 scores (r = 0.637; p = 0.000). Conclusion: There is a significant positive correlation between caries status (DMF-T) and quality of life (OHIP-14) in the elderly. The higher the dental caries index, the lower the quality of life (the higher the OHIP-14 score) in this elderly population.